National culture and expatriate deployment - Brock, David M; Shenkar, Oded; Shoham, Amir; Siscovick, Ilene C (Journal of International Business Studies, 2008)
We hypothesize that expatriate deployment is a control function predicted by home country culture dimensions with transaction cost and agency repercussions (rather than culture in the aggregate). This departure from the traditional conceptualization and measurement of cultural impact also yields a hypothesized asymmetrical effect, which is tested for a multi-country sample of 236 multinational subsidiaries. Using multiple measures of national culture, hypotheses are supported, with assertiveness and power distance confirmed as prime predictors of expatriate deployment.